The transition period in soccer: A window of opportunity - Silva, J. R.; Brito, J.; Akenhead, R.; Nassis, G. P. (Sports Medicine, 2016)
The aim of this paper is to describe the physiological changes that occur during the transition period in soccer players. A secondary aim is to address the issue of utilizing the transition period to lay the foundation for the succeeding season. We reviewed published peer-reviewed studies if they met the following three selection criteria: (1) the studied population comprised adult soccer players (aged >18 years), (2) time points of physiological and performance assessments were provided, and (3) appropriate statistics for the calculation of effect sizes were reported. Following two selection phases, 12 scientific publications were considered, involving a total sample of 252 players. The transition period elicits small to moderate negative changes in body composition, a moderate decline in sprint performance with and without changes of direction, and small to moderate decrements in muscle power. Detraining effects are also evident for endurance-related physiological and performance outcomes: large decrements in maximal oxygen consumption (VO2max) and time to exhaustion, and moderate to very large impairments have been observed in intermittent-running performance. Off-season programs should be characterized by clear training objectives, a low frequency of training sessions, and simple training tools in order to facilitate compliance. The program suggested here may constitute the `minimum effective dose` to maintain or at least attenuate the decay of endurance- and neuromuscular-related performance parameters, as well as restore an adequate strength profile (reduce muscle strength imbalances). This periodization strategy may improve the ability of players to cope with the elevated training demands of pre-season training and therefore reduce the risk of injury. Moreover, this strategy will favor a more efficient development of other relevant facets of performance during the pre-competition phase (e.g., tactical organization). We contend that the transition period needs to be perceived as a `window of opportunity` for players to both recover and `rebuild` for the following season.